Single-cell RNA Sequencing Reveals Heterogeneity of Cultured Bovine Satellite Cells - Lyu, Pengcheng; Qi, Yumin; Tu, Zhijian J.; Jiang, Honglin (Frontiers in Genetics, 2021)
Skeletal muscle from cattle is a major source of food for humans. To improve muscle growth or quality in cattle, it is necessary to understand the mechanisms that govern skeletal muscle composition and growth. Satellite cells are the myogenic progenitor cells in postnatal skeletal muscle. In this study we analyzed the composition of satellite cells from a two-week-old male calf with scRNA-seq using the 10x Genomics platform. Sequencing of two scRNA-seq libraries yielded 860 million reads. These reads represented 19,096 individual cells and 15 cell clusters that differed in gene expression profile. Based on the enriched expression of markers of satellite cells (PAX7 and PAX3), markers of myoblasts (MYOD1, MYF5, DES), and markers of differentiated myoblasts or myocytes (MYOG, MYMK), 3 clusters were determined to be satellite cells, 2 clusters myoblasts, and 2 clusters myocytes. Gene ontology analyses of upregulated genes indicated that cells in these clusters differed in proliferation rate and differentiation stage. Two of the remaining clusters were enriched with PDGFRA, a marker of fibro-adipogenic (FAP) cells, the progenitor cells for intramuscular fat, and are therefore considered to be FAP cells. Gene ontology analyses indicated active lipogenesis in one of these two clusters. The identity of the remaining 6 clusters could not be defined. Overall, the results of this study support the hypothesis that bovine satellite cells are composed of subpopulations that differ in transcriptional status and myogenic potential. The results of this study also support the hypothesis that intramuscular fat in cattle originates from fibro-adipogenic cells.